b - Norwich, Brahm (Routledge : London, 2008)
Inclusion has become very influential internationally in the field of schooling. This has involved the introduction of policies that pursue more provision for, and acceptance of, students with special educational needs or disabilities in ordinary school settings. However, these policies represent different and often conflicting values and approaches to education. The basic dilemma of difference is whether to recognise or not to recognise differences, as either way there are negative implications or risks associated with stigma, devaluation, rejection or denial of relevant opportunities. This book examines the ideas about these dilemmas from a range of disciplines and fields about the nature and origins of such dilemmas as they apply to special and inclusive education including identification, curriculum, and placement.
Includes bibliographical references and index.
Keywords: Special education -- Great Britain; Children with disabilities -- Identification -- Great Britain; Special education -- United States